Effect of varieties and spacings on growth, yield and quality of patchouli (Pogostemon patchouli Pellet.) - Farooqi, K N Srinivasappa, K M Ramachandra, M Vasundhara, A A (Journal of Spices and Aromatic Crops, 2003)
Two varieties of patchouli (Pogostemon patchouli Pellet.) were evaluated at different plant densities. The experiment consisted of eight treatments comprising the varieties Johore and Java and four spacings (60 x 60, 60. x 45, 45 x 45 and 45 x 30 cm). The results revealed significant differences in performances of varieties at different spacings. Java variety was more robust and yielded higher dry herbage compared to Johore. However Johore yielded more oil content (2.7%) and higher patchouli alcohol (44.7%) as compared to Java (1.4% & 34.5%, respectively). Among the different spacings, Java recorded higher cumulative dry herbage (4.21 t ha-1) and oil yield (60.65 I ha-1) under 60 x 45 cm spacing, where as 45 x 45 cm spacing was found to be the best for Johore, recording more cumulative dry herbage (3.15 t ha-1) and oil yield (86.52 t ha-1).